Capital social, redes sociais e inovações produtivas - PONTE, Tereza Maria Ferreira Ximenes (2015)
Successful experiences in motivating local populations show the importance of organizing people and training them to develop innovative projects. It also reveals that communities in which people interact more frequently with each other and where social networks, on a whole, are well integrated, are more likely to overcome their limitations and to take advantage of their opportunities. This in return favors the development of strategies and collective tactics, increasing the power of choice and decision of the community members.